2021
DOI: 10.5114/pjp.2021.111776
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of potential molecular targets of desmoid-type fibromatosis

Abstract: Desmoid-type fibromatosis is locally aggressive tumor rare in general population, although commonly present in patients with familial adenomatous polyposis, significantly contributing to the morbidity and mortality of patients. To optimize and individualize the management of patients it is necessary to better understand the biology of these tumors. Immunohistochemical analysis of β-catenin, VEGF, hormone receptors ERβ, ERα and PR, COX-2, APC protein, EGFR, c-kit (CD117), bcl-2 and HER2 expression, potential th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It has already been approved for the management of soft-tissue sarcomas [97]. VEGF overexpression has been identified as a common feature in both sporadic and FAP-associated DTs [98,99]. A clinical trial of pazopanib (800 mg per day orally for up to 1 year) demonstrated its efficacy in the treatment of DTs in a phase II trial compared with cytotoxic chemotherapy of MTX and VBL (intravenous MTX (30 mg/ m 2 ) plus VBL (5 mg/m 2 ) once a week for 6 months and then every 2 weeks for 6 months), with 84% vs. 45% 6-month progression-free rates, respectively [100].…”
Section: ) Tyrosine Kinase Inhibitors (Tki)mentioning
confidence: 99%
“…It has already been approved for the management of soft-tissue sarcomas [97]. VEGF overexpression has been identified as a common feature in both sporadic and FAP-associated DTs [98,99]. A clinical trial of pazopanib (800 mg per day orally for up to 1 year) demonstrated its efficacy in the treatment of DTs in a phase II trial compared with cytotoxic chemotherapy of MTX and VBL (intravenous MTX (30 mg/ m 2 ) plus VBL (5 mg/m 2 ) once a week for 6 months and then every 2 weeks for 6 months), with 84% vs. 45% 6-month progression-free rates, respectively [100].…”
Section: ) Tyrosine Kinase Inhibitors (Tki)mentioning
confidence: 99%